Effects of gastrointestinal symptoms on the efficacy of washed microbiota transplantation in patients with autism - Hu, Dong-Xia; Lu, Cai-Mei; Si, Xin-Yu; Wu, Qing-Ting; Wu, Li-Hao; Zhong, Hao-Jie; He, Xing-Xiang (Frontiers in Pediatrics, 2025)
ObjectiveWashed microbiota transplantation (WMT) has emerged as a promising therapeutic strategy for autism spectrum disorder (ASD), though the factors that influence its efficacy remain poorly understood. This study explores the impact of gastrointestinal (GI) symptoms on the effectiveness of WMT in ASD.MethodsClinical data encompassing ASD symptoms, GI disturbances, and sleep disorders were collected from patients with ASD undergoing WMT. The therapeutic impact of WMT and the contributing factors to its efficacy were assessed.ResultsWMT significantly reduced scores on the Aberrant Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Sleep Disturbance Scale for Children (SDSC), alongside a significant reduction in the incidence of constipation, abnormal stool forms, and diarrhea (all p < 0.05). After six courses of WMT, substantial reductions were observed in ABC, CARS, and SDSC scores, with increased treatment courses correlating with greater improvement (p < 0.05). Multiple linear regression analysis revealed that WMT efficacy was enhanced in patients with pre-existing GI symptoms (diarrhea: β = 0.119, p < 0.001; abnormal stool form: β = 0.201, p < 0.001) and those receiving a higher number of treatment courses (β = 0.116, p < 0.001). Additionally, the analysis indicated that treatment outcomes were more favorable in patients who had not undergone adjunct interventions (β = −0.041, p = 0.002), had a longer disease duration (β = 0.168, p = 0.007), and exhibited more severe disease symptoms (β = 0.125, p < 0.001).ConclusionWMT significantly alleviates both ASD and GI symptoms, along with sleep disturbances, in affected individuals. Six treatment courses resulted in notable improvement, with increased course numbers further improving therapeutic outcomes. Furthermore, pre-treatment GI symptoms, such as diarrhea and abnormal stool forms, may influence the effectiveness of WMT. Notably, patients who did not receive additional interventions, had a prolonged disease duration, and presented with more severe symptoms experienced markedly improved treatment responses.